The Practice and Application of AR Games to Assist Children's English Pronunciation Teaching. - Hu, Liang; Yuan, Yuan; Chen, Qing; Kang, Xiangying; Zhu, Yan (Occupational Therapy International, 2022)
This paper conducts an in-depth study and analysis of the practice and application of teaching English pronunciation to children using AR (augmented reality) game assistance. The article analyzes the design of AR educational games based on the concept of learning behavior input, clarifies and determines the factors influencing students' learning behavior input in AR gamified teaching environment, and proposes the design principles of AR educational games based on learning behavior input. By analyzing the characteristics of experiential learning and AR, the model of AR-based English experiential learning activities for elementary school is established. Based on certain demand analysis, the AR software that can be used for teaching pronunciation in elementary school English classrooms was designed and developed using Unity3D and 3ds Max software. The experimental method was used to compare and apply the software in the target school, and the students of elementary school X were selected as the experimental subjects. The data were analyzed with the help of SPSS and NVivo software, and the questionnaire was used to measure the "ease of use," "usefulness," and "satisfaction with the software." The questionnaire was used to measure students' acceptance of AR software in three dimensions: "ease of use," "usefulness," and "satisfaction with the software."